Penerapan Game-Based English Learning untuk Penguatan Nilai Karakter dan Keterampilan Anak Usia Sekolah Dasar dan Menengah di Tanoker Ledokombo - Indrastana, Nodistya Septian; Rukiati, Enik; Rinda, Renata Kenanga; Dewangga, Vigo; Ningsih, Yuslaili; Norwahi, Nur Aqilah Binti (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2026)
English proficiency is one of the essential competencies for young generations in today’s global context. However, the reality in rural areas of Indonesia indicates that English learning still faces various limitations, particularly in terms of teaching methods, supporting facilities, and the integration of character education. This community service program aimed to improve basic English skills while fostering positive character values among elementary to lower secondary school students through the implementation of a game-based learning approach at Yayasan Tanoker Ledokombo, Kabupaten Jember, as the community partner. The program was conducted through three main stages: preparation, implementation, and evaluation. The results revealed an increase in students’ active participation, learning motivation, and understanding of basic English vocabulary and expressions. Additionally, collaborative game-based activities contributed to the development of character values, including cooperation, responsibility, and sportsmanship. These findings suggest that game-based learning serves as an effective and relevant approach to English language learning in supporting character development within non-formal rural education settings.